Secretory phospholipase A(2) group IIA modulates insulin sensitivity and metabolism - Kuefner, Michael S. (J Lipid Res, 2017)
Secretory phospholipase A(2) group IIA (PLA2G2A) is a member of a family of secretory phospholipases that have been implicated in inflammation, atherogenesis, and antibacterial actions. Here, we evaluated the role of PLA2G2A in the metabolic response to a high fat diet. C57BL/6 (BL/6) mice do not express PLA2g2a due to a frameshift mutation. We fed BL/6 mice expressing the human PLA2G2A gene (IIA+ mice) a fat diet and assessed the physiologic response. After 10 weeks on the high fat diet, the BL/6 mice were obese, but the IIA+ mice did not gain weight or accumulate lipid. The lean mass in chow- and high fat-fed IIA+ mice was constant and similar to the BL/6 mice on a chow diet. Surprisingly, the IIA+ mice had an elevated metabolic rate, which was not due to differences in physical activity. The IIA+ mice were more insulin sensitive and glucose tolerant than the BL/6 mice, even when the IIA+ mice were provided the high fat diet. The IIA+ mice had increased expression of uncoupling protein 1 (UCP1), sirtuin 1 (SIRT1), and PPARγ coactivator 1α (PGC-1α) in brown adipose tissue (BAT), suggesting that PLA2G2A activates mitochondrial uncoupling in BAT. Our data indicate that PLA2G2A has a previously undiscovered impact on insulin sensitivity and metabolism.